Comparative Analysis of Flooding in Mandra, Athens 2017 and Western Attica, Athens 1961: Actions, Response and Human Resources - Zacheilas, Christos (Advances in Social Sciences Research Journal, 2019)
On November 15, 2017 a flash flood struck West Attica with intense effects in Mandra and other cities, leading to many people going missing and causing the death of many people as well as material damages. Another storm took place during November 1961 with 40 victims and countless material damages as well. This study investigates the flooding problems and its consequences in Mandra (2017) and Western Attica (1961) and whether the Greek State is working in a direction of resilience and sustainability to avoid substantial damage in the future. Civil Protection, education and flood risk management play a lifesaving and life-sustaining role in an emergency situation and are the mechanisms that are crucial in order to prevent and mitigate damage.